1970
DOI: 10.1063/1.1673622
|View full text |Cite
|
Sign up to set email alerts
|

Noniterative Solutions of Integral Equations for Scattering. III. Coupled Open and Closed Channels and Eigenvalue Problems

Abstract: The homogeneous integral solution formalism developed by Sams and Kouri is applied to the problems of coupled open- and closed-channel radial equations and coupled radial eigenvalue equations. The problem of coupled eigenvalue equations is considered first. Because we deal with the integral equation form of the Schrödinger equation, the proper solutions may be obtained by integrating from the origin outward, rather than both outward from and inward toward the origin. For the case of eigenvalue radial equations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The Feshbach projection operator approach was first introduced in nuclear physics (Feshbach, 1962) and was later used in molecular quantum scattering (Sams and Kouri, 1970). We have adapted this approach for the acoustic problem.…”
Section: Construction Of the Projection Operatormentioning
confidence: 99%
See 1 more Smart Citation
“…The Feshbach projection operator approach was first introduced in nuclear physics (Feshbach, 1962) and was later used in molecular quantum scattering (Sams and Kouri, 1970). We have adapted this approach for the acoustic problem.…”
Section: Construction Of the Projection Operatormentioning
confidence: 99%
“…(Kosloff and Kessler, 1987) removed all evanescent components (growing and decaying) to make their solution stable, but they thereby lose the decaying evanescent waves that make a contribution to large dip scattering and can be very important. We have used the Feshbach projection method, developed in nuclear physics and adapted to chemical physics (Feshbach, 1962;Sams and Kouri, 1970) to remove only growing evanescent waves whereas the decaying evanescent waves and all propagating waves ("up" and "down") are retained.…”
Section: Introductionmentioning
confidence: 99%
“…(15) and (16), and integrating over all target and angular-continuum coordinates convert Eq. (13) into a radial set of coupled integral equations of the general form (1 -G U)f=G where the matrices have the form (21) [U]pq --V p(r, )cu;t " (22) radial coordinate from r; i to r, . We have found that a standard mesh of 60 points and five zones of the form (10,20, 10,15,5/O.…”
Section: Formalismmentioning
confidence: 99%
“…Therefore, by closing the channels, we convert to an eigenvalue problem [21] whose solution exists only at a discrete set of allowed values of E. These values represent the bound energies of the composite system. Sams and Kouri [22] showed that at these discrete energies E;, the determinant of the matrix M defined by…”
Section: Formalismmentioning
confidence: 99%